2013
DOI: 10.1139/cjpp-2012-0307
|View full text |Cite
|
Sign up to set email alerts
|

Functional foods and nutraceuticals as therapeutic tools for the treatment of diet-related diseases

Abstract: In Western societies, the incidence of diet-related diseases is progressively increasing due to greater availability of hypercaloric food and a sedentary lifestyle. Obesity, diabetes, atherosclerosis, and neurodegeneration are major diet-related pathologies that share a common pathogenic denominator of low-grade inflammation. Functional foods and nutraceuticals may represent a novel therapeutic approach to prevent or attenuate diet-related disease in view of their ability to exert anti-inflammatory responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 150 publications
1
46
0
Order By: Relevance
“…This aspect was very well recognized by Hippocrates, the Father of Medicine, who proclaimed almost 25 centuries ago, “Let food be thy medicine and medicine be thy food.” To further substantiate the importance and relevance of this adage, observations from around the world clearly indicate that the incidence of diet-related diseases is progressively increasing due to greater availability of hypercaloric food and a sedentary lifestyle, which cause low-grade inflammation in the individual. [18]…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…This aspect was very well recognized by Hippocrates, the Father of Medicine, who proclaimed almost 25 centuries ago, “Let food be thy medicine and medicine be thy food.” To further substantiate the importance and relevance of this adage, observations from around the world clearly indicate that the incidence of diet-related diseases is progressively increasing due to greater availability of hypercaloric food and a sedentary lifestyle, which cause low-grade inflammation in the individual. [18]…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…[18] All these properties are extremely beneficial in the prevention and mitigation of the IBD. Studies have shown that the dietary agents like apple, bilberry, black raspberry, cocoa, bael, green tea (綠茶 Lǜ Chá); spices like garlic (大蒜 Dà Suàn), Malabar tamarind, saffron (番紅花 Fān Hóng Huā), fenugreek, ginger (生薑 Shēng Jiāng), turmeric (薑黃 Jiāng Huáng); oil of olive; nutraceuticals like grape seed polyphenols; and the dietary phytochemicals like resveratrol, ellagic acid, zerumbone, quercetin, kaempferol, rutoside, and rutin are consumed regularly and are commonly used.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Therefore the health benefits of plant food-based diets could be related to both integrated antioxidant and anti-inflammatory mechanisms exerted by a wide array of phytochemicals present in fruit, vegetables, herbs and spices [21-24]. On this basis, there is mounting interest in identifying foods, food extracts and phytochemicals formulations from plant sources which are able to efficiently modulate oxidative and inflammatory stress to prevent diet-related diseases [25]. This paper reviews available evidence about the effect of supplementation with selected fruits, vegetables, herbs, spices, cocoa, beverages with mixed plant food composition as well as extracts and galenic formulation, on combined markers of redox and inflammatory status in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prevention and treatment of obesity are extremely important to reduce the risks of developing lifestyle-related diseases. Many studies have reported that dietary polyphenols exert anti-obesity effects 1 .…”
Section: Introductionmentioning
confidence: 99%